Experimentos sobre leis de conservação para o ensino de física no ensino médio baseados em tecnologias livres - Meucci, Ricardo Dalke (2014)
This research investigates the possible use of Information Technology and Communication, based on open technologies and the study of conservation laws in secondary education, providing meaningful learning, using Ausubel as reference. Four activities were executed using the Video Review technique, and performed by students on second grade of high school at Military Police of Paraná High School during the year of 2013. Throughout the development of the activities, it was clearly demonstrated a major evolution of the quality of student’s responses, which can be determined by the extent of the responses, the improvement on the vocabulary and the construction of arguments to support a certain point of view. As a result, the proposed activities showed evidence of meaningful learning. These activities also showed the possibility of extending the physics lessons beyond technical skills and reaching other areas of learning, such as the skills and abilities required by ESMS, which goes beyond a vision based simply on the subject content.